PENGGUNAAN MEDIA MANIPULATIF DALAM KEGIATAN MENGENAL KONSEP BILANGAN DI TK KRISTEN IMMANUEL PONTIANAK SELATAN - Septiviani, Euvemia; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
This research aims to describe the use of manipulative media in activities to recognize the concept of numbers at the Immanuel Christian Kindergarten in South Pontianak. The research method used is descriptive qualitative with a qualitative approach. The subjects in this research were two class teachers who taught group B. The results of the research showed that the activities to recognize the concept of numbers at the Immanuel Christian Kindergarten in South Pontianak consisted of 3 stages, namely planning, implementation and evaluation. 1) Planning, carried out by making a lesson plan as a learning reference to achieve learning objectives, preparing material, delivery method, and preparing media, 2) Implementation, carried out by giving children teaching according to the lesson plan and the teacher fills the remaining time by introducing the concept of numbers using media manipulatives so that children better understand the concept of numbers. The indicators used are counting/mentioning the sequence of numbers 1-20, counting (recognizing the concept of numbers with objects) 1-20, ordering number symbols with objects 1-20 and connecting/pairing number symbols with objects 1-20 3) Evaluation, reflecting at the end of the activity, asking what was learned today, repeating the material taught, testing the extent of children's understanding of the concept of numbers, providing motivation and assignments at home as well as assessment in the form of anecdotal notes at the end of the semester